Limits on integrating motion information across saccades - Dahlstrom-Hakki, Ibrahim; Pokkatsek, Akexabder (Perception & psychophysics, 2006)
In two experiments, we investigated whether people could detect changes in the rotary motion of a cube. A rendering of a cube rotating at a constant angular velocity was presented on a video monitor and, at a key point in the trial, a cross was presented to one side of the cube as a cue for a saccade. On some trials, a change in the rotation occurred either about 100 msec before the saccade or during the saccade; on other trials, there was no change. The change consisted of moving the cube to a new position in the "rotation sequence," after which it continued to rotate at the same angular velocity as before. There was also a control on all trials to ensure that change detection was not due to the detection of low-level motion. Although detection of the change was well above chance when it occurred during the fixation, it was at chance when it occurred during the saccade, except in the case of one participant (who was in both experiments). This chance performance also occurred in Experiment 2 for (1) a slower rotation speed and (2) an axis of rotation that made the rotation planar. The participant who had above chance performance (and as good as that when the change occurred during a fixation) reported using a "strategy" that did not track the path of the cube. It thus appears that there is no natural way in which the visualsystem tracks this rotary motion, and that detection of change requires some sort of recoding. This finding raises the question of whether good performance in other, apparently similar, motion-detection tasks is a result of similar recoding.